Effect of thermal environment on sleep quality in actual bedroom in summer by sleep stages analysis - Yuichi Akiyama; Emika Miyake; Riho Matsuzaki; Masayuki Ogata; Kazuyo Tsuzuki; Shin‐ichi Tanabe (Japan Architectural Review, 2021)
Abstract This field survey was conducted during summer in actual bedrooms and used polysomnography to evaluate the effect of thermal environment on sleep quality by analyzing electroencephalogram, electro‐oculogram, and electromyogram signals, which were continuously measured during sleep. It was found that the effect of the thermal environment (ie, air temperature, air velocity, and air turbulence) on sleep quality varied according to the sleep cycle and stages. The effect of air turbulence depended mainly on the air temperature. At low or neutral temperatures, air turbulence had negative effects on sleep quality, whereas under warm temperatures, air turbulence had negligible effects on sleep quality.